Pendidikan Kreatif Berbasis Nilai-Nilai Islam Melalui Public Literacy: (Studi Kasus di Komunitas Gubuk Literasi Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo) - Sigit Dwi Laksana (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2019)
The lack of interest reading in Ponorogo community makes a lack of knowledge, proven by at least libraries or bookstores in Ponorogo. This triggered the presence of several literacy communities or literacy activists, one of them was the Gubuk Literasi community which was initiated by Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo which later opened one of its activities, namely a reading park or an open library in a public area. This study aims to describe the forms, applications and supporting and inhibiting factors of creative education based on Islamic values ​​through a public lieracy case study in the Gubuk Literasi community. Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo in the form of scientific development activities such as holding reading stalls (parks reading) routinely, discussions between managers and members with the insertion of Islamic values, and instilling the spirit of the importance of reading and eradicating illiteracy in the community. Data collection uses interview, observation and documentation methods. The data analysis that the researcher used in this research was descriptive qualitative, that is the data that had been collected was compiled and classified so that it could answer the problem formulation. This research is a qualitative research with the subject of the research being the chairperson of the Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo, the coordinator and manager of the Gubuk Literasi community, and the people who are interested or visitors of the Gubuk Literasi community. While the objects in this study are forms of creative activities that are packaged by community managers, so that they are able to become a forum for education and scientific repertoire and the efforts of managers to insert Islamic values ​​in their movements in the Gubuk Literasi community. The results of the study show that forms of creative education based on Islamic values ​​through public literacy (case studies in the Gubuk Literasi Community area Pimpinan Daerah Ikatan Pelajar Muhammadiyah Ponorogo) are children to understand the story and imitate the morals in the story through the story told (read ) or reading, born in the form of a literati activist who builds science, becomes a growing interest in reading in the community, the members of the community are grown to insert verses in the Quran in their discussions.